Heparan Sulfate Proteoglycan Binding Properties of Adeno-Associated Virus Retargeting Mutants and Consequences for Their In Vivo Tropism - Perabo, Luca (American Society for Microbiology, 2006)
Adeno-associated virus type 2 (AAV-2) targeting vectors have been generated by insertion of ligand peptides into the viral capsid at amino acid position 587. This procedure ablates binding of heparan sulfate proteoglycan (HSPG), AAV-2's primary receptor, in some but not all mutants. Using an AAV-2 display library, we investigated molecular mechanisms responsible for this phenotype, demonstrating that peptides containing a net negative charge are prone to confer an HSPG nonbinding phenotype. Interestingly, in vivo studies correlated the inability to bind to HSPG with liver and spleen detargeting in mice after systemic application, suggesting several strategies to improve efficiency of AAV-2 retargeting to alternative tissues.